The effect of high-flow arteriovenous fistulas on systemic haemodynamics and brain oxygenation - Malik, Jan; Valerianova, Anna; Tuka, Vladimir; Trachta, Pavel; Bednarova, Vladimira; Hruskova, Zdenka; Slavikova, Marcela; Rosner, Mitchell H; Tesar, Vladimir (ESC heart failure, 2021)
AIMS: High-flow arteriovenous fistula (AVF) for haemodialysis leads to profound haemodynamic changes and sometimes to heart failure (HF). Cardiac output (CO) is divided between the AVF and body tissues. The term effective CO (COef) represents the difference between CO and AVF flow volume (Qa) and better characterizes the altered haemodynamics that may result in organ hypoxia. We investigated the effects of Qa reduction on systemic haemodynamics and on brain oxygenation. METHODS AND RESULTS: This is a single-centre interventional study. Twenty-six patients on chronic haemodialysis with high Qa (>1500 mL/min) were indicated for surgical Qa reduction for HF symptoms and/or signs of structural heart disease on echocardiography. The included patients underwent three sets of examinations: at 4 months and then 2 days prior and 6 weeks post-surgical procedure. Clinical status, echocardiographical haemodynamic assessment, Qa, and brain oximetry were recorded. All parameters remained stable from selection to inclusion. After the procedure, Qa decreased from 3.0 ± 1.4 to 1.3 ± 0.5 L/min, P < 0.00001, CO from 7.8 ± 1.9 to 6.6 ± 1.5 L/min, P = 0.0002, but COef increased from 4.6 ± 1.4 to 5.3 ± 1.4 L/min, P = 0.036. Brain tissue oxygen saturation increased from 56 ± 11% to 60 ± 9%, P = 0.001. CONCLUSIONS: Qa reduction led to increased COef. This was explained by a decreased proportion of CO running through the AVF in patients with Qa > 2.0 L/min. These observations were mirrored by higher brain oxygenation and might explain HF symptoms and improved haemodynamics even in asymptomatic high Qa patients.
Keywords: Brain oximetry; Renal Dialysis; Brain; dialýza ledvin; Arteriovenous Fistula; Effective cardiac output; arteriovenózní píštěl; mozek; Humans; Arteriovenous fistula; Hemodynamics; Arteriovenous Shunt, Surgical; arteriovenózní zkrat; hemodynamika; High-output heart failure; lidé